Evaluation of Anterior Segment Parameters and Possible Influencing Factors in Normal Subjects Using a Dual Scheimpflug Analyzer - Wang, Xiaogang; Dong, Jing; Wu, Qiang (PloS one, 2014)
To investigate normal anterior segment parameters and analyze the possible influencing factors using a dual Scheimpflug system. Department of Ophthalmology, Affiliated Sixth People's Hospital Shanghai Jiao Tong University, Shanghai, China. A prospective observational case series. A total of 153 normal subjects (153 eyes) were studied. The anterior segment parameters, including the central corneal thickness (CCT), anterior chamber depth (ACD), pupil diameter (PD), keratoconus prediction index (KPI), simulated keratometry (SimK) values, anterior instantaneous curvature (AIC), posterior axial curvature (PAC), corneal eccentricity, total corneal power (TCP), axial curvature (AC), total corneal wavefront (TCW), high order aberration (HOA), and spherical aberration (SA), were determined using a dual Scheimpflug analyzer. The CCT and ACD were both negatively correlated with age (r = -0.203, p = 0.012; r = -0.589, p<0.001). There was no significant difference in the refractive indices of AIC and SimK. Compared with the negative correlation of HOA and SA (r = -0.358, p<0.001), a positive correlation was found between TCW and HOA (r = 0.561, p<0.001). Unlike the decreased tendency of AC, the TCP increased gradually from the center to the periphery in the central 8 mm diameter. TCP showed a significant correlation with AC in the analyzed area. AIC and SimK provide different information in clinic, but the refractive indices of them showed no difference in this healthy study population, and age should be considered when using CCT and ACD values.